Factors associated with the development of healthcare-associated infections in the intensive care unit: a literature review (Research, Society and Development, 2022)
Infection is a common occurrence among intensive care unit (ICU) patients and a prerequisite for the development of sepsis. Patients treated in the ICU are at increased risk of healthcare-associated infections (HAIs) due to the invasive nature of many treatments, such as mechanical ventilation, urinary catheterization, and central venous access. The present study aims to describe the factors that lead to the development of infection related to health care in the intensive care unit. This is a study with a qualitative approach, where an integrative literature review was adopted, carried out through the Virtual Health Library (VHL) in Pubmed databases, using the crossings of the English descriptors “Hospital infections”, “Intensive care unit” and “health care”. For the evaluation of the research problem and its stratification, the PVO strategy was used. The following guiding question was formulated: What are the factors that lead to the emergence of infections in the intensive care unit? Nosocomial infections in intensive care units are most commonly associated with invasive treatments and diagnostic techniques, as well as the use of life support or monitoring devices directly or indirectly. Gram-negative microorganisms were identified more frequently than gram-positive microorganisms in the culture. Advanced age, comorbid metastatic cancer, HIV infection, and heart failure were independently associated with a higher risk of death. This variation was associated with patient and disease-specific factors and the care process and country-to-country differences.